It's in the eye of the beholder: visual lateralisation in response to the social environment in poeciliids. Issue 5 (12th April 2019) - Fuss, Theodora; Nöbel, Sabine; Witte, Klaudia
Abstract : The social environment offers fish complex information about the quality, performance, personality and other cues of potential mates and competitors simultaneously. It is likely, therefore, that the environmental information regarding the context of mate choice is perceived and processed differently in species and sexes in respect to lateralisation. The present study comparatively assessed visual lateralisation behaviour in response to different social or sexual stimuli in three closely related poeciliid species ( P. latipinna, P. mexicana, P. formosa ) in comparison to a more distantly related species ( P. reticulata ). Individuals were presented with four different social or sexual stimuli that were tested against a control stimulus; (a) a conspecific male, (b) a conspecific female, (c) a heterosexual conspecific pair, (d) three conspecific females (shoal). In order to approach a target stimulus, focal fish had to perform detours to the right or left of a vertically straight‐shaped barrier. The three closely related poeciliid species, P. latipinna, P. mexicana, P. formosa, appeared to have a general tendency to turn right ( i.e ., left‐eye preference), whereas the more distantly related P. reticulata males and females showed an overall bias to the left ( i.e ., right‐eye preference) in response to various social–sexual incitements. Moreover, body size seemed to significantly influence especially the males' detour behaviour, with smaller males acting in opposition to their larger conspecifics in response to certain social stimuli. In this case, smaller and larger Poecilia spp. males responded in the same way as smaller and larger males of the other three poeciliid species. Therefore, results possibly point to differences in the degree of general social behaviour between closely and more distantly related species and mating motivation amongst larger and smaller individuals when placed in a novel social environment. Hence, present results possibly suggest a sex‐specific functional lateralisation for the analysis of visual information and seem to support the closer ancestral relationships between the Poecilia spp. tested in this study and the more distantly related guppies in terms of their left–right lateralisation. Generally, present results suggest that functional asymmetries in behaviour could be widespread among vertebrates, thus supporting the hypothesis of an early evolution of lateralisation in brain and behaviour.